Assessment of Anxiety and Hemodynamic Changes Pre and Post-Oral Implant Surgery - De Romero, Beatriz Cepeda; Paba, Juliana Lobo; Ramirez, Cristian Diaz; Tellez, Diego Alejandro Diaz (British Journal of Healthcare and Medical Research, 2024)
Dental anxiety is the fifth most common cause of anxiety. Patient anxiety is observed in situations involving anesthetic injections, use of rotary instruments. Local anesthetics are used in conjunction with vasoconstrictors, to prolong their action at the applied site and prevent dissemination to the bloodstream and the presence of multisystemic adverse reactions.. Method: Clinical, observational, analytical research longitudinal cohort with minimal risk. It shows 40 patients with voluntary participation, over 18 years of age, healthy use of articaine 4% with epinephrine 1:100,000. Pre-anesthesia: assessment of the degree of anxiety using the Modified Corah Dental Anxiety Scale. Blood pressure and heart rate in three stages: pre-anesthesia, 10 minutes post-anesthesia and at the end of the surgical procedure using a digital blood pressure monitor (SCANMED)® and the percentage of oxygen saturation with oximeter (OMRON).® Results: Mean age 56.7 ± 13.1 years, women 26 (65%), men 14 (35%); no pre-existing diseases (60%),. Surgical time (2 hours and 15 minutes). The most commonly used type of surgery is of medium complejidad.In the three times evaluated by the Cochrane Q test, there was a significant difference in the values of systolic pressure (P=0.001), diastolic pressure (P=0.037), Heart rate variations (P=0.660). and moderate anxiety 16 (40%) were present using the Modified Corah Dental Anxiety Scale.Conclusion: Older adults with dental implant surgery presented mild or moderate anxiety, without significant changes in blood pressure and oxygen saturation, 10 minutes after the administration of local anesthesia and at the end of the surgical procedure.